2005
DOI: 10.1021/jf051333o
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Compounds from Blueberries Can Inhibit Colon Cancer Cell Proliferation and Induce Apoptosis

Abstract: Research has shown that diets rich in phenolic compounds may be associated with lower risks of several chronic diseases including cancer. This study systematically evaluated the bioactivities of phenolic compounds in rabbiteye blueberries and assessed their potential antiproliferation and apoptosis induction effects using two colon cancer cell lines, HT-29 and Caco-2. Polyphenols in three blueberry cultivars, Briteblue, Tifblue, and Powderblue, were extracted and freeze-dried. The extracts were further separat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
161
2
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(176 citation statements)
references
References 40 publications
8
161
2
5
Order By: Relevance
“…The most striking antioxidant activity is cyaniding 3-galactose. DPPH assays showed that it was more effevtive than flavonol glycoside and the standards in scavenging free radicals, with an EC50 of 7.7 M compared to 17.3 M for myricetin 3-arabinoside and 30 M for trolox standard [4,130,131] Increased plasma antioxidant status, protected RBC against hemolysis [126,132] Showed protective effects on PC12 cells damage and chronic diseases associated with oxidative stress [133] Showed neuro and mitochondrio-protective effect [134] Antioxidant Activities Showed antioxidative activity under the used assay conditions towards prevention of oxidative DNA damage [135] Inhibited proliferation of MCF-7, MDA-MB-231 and MDA-MB-435 breast cancer cells [4,8,126,127] Inhibited the induction of ornithine decarboxylase, an enzyme involved in tumor proliferation, and induce quinine reductase, an enzyme that can inactivate certain carcinogens [136] Exhibited the human colon tumor cell lines Caco-2, HT-116, and HT-29 [10,137,138] Exhibited the anticancer effects on DLD-1 and COLO205 cells [139] Inhibited matrix metalloproteinase activity in DU145 human prostate cancer cells [140] Exhibition of anticancer capability in human lung and leukemia cells [105] Modulated the expression of cyclooxygenase-2 (COX-2) and I B in human colon cancer cells [141] Cytotoxicities Inhibitory effect on activator protein-1, nuclear factor-B, and mitogen-activated protein kinases activation [105,142] Prevented the urinary tract infections [143] Showed potential inhibitory effect against bacteria involved in dental caries and periodontal diseases [147,148] Exhibited potent biological activity by inhibiting adherence of uropathogenic isolates of P-fimbriated Escherichia coli bacteria to cellular surfaces containing -Gal(1 4)--Gal receptor sequences similar to those on epithelial cells in the urinary tract [149,150] Antimicrobial Activities…”
Section: Biosynthesis Pathways Of Anthocyanins and Flavonoids (Fig 3mentioning
confidence: 99%
See 2 more Smart Citations
“…The most striking antioxidant activity is cyaniding 3-galactose. DPPH assays showed that it was more effevtive than flavonol glycoside and the standards in scavenging free radicals, with an EC50 of 7.7 M compared to 17.3 M for myricetin 3-arabinoside and 30 M for trolox standard [4,130,131] Increased plasma antioxidant status, protected RBC against hemolysis [126,132] Showed protective effects on PC12 cells damage and chronic diseases associated with oxidative stress [133] Showed neuro and mitochondrio-protective effect [134] Antioxidant Activities Showed antioxidative activity under the used assay conditions towards prevention of oxidative DNA damage [135] Inhibited proliferation of MCF-7, MDA-MB-231 and MDA-MB-435 breast cancer cells [4,8,126,127] Inhibited the induction of ornithine decarboxylase, an enzyme involved in tumor proliferation, and induce quinine reductase, an enzyme that can inactivate certain carcinogens [136] Exhibited the human colon tumor cell lines Caco-2, HT-116, and HT-29 [10,137,138] Exhibited the anticancer effects on DLD-1 and COLO205 cells [139] Inhibited matrix metalloproteinase activity in DU145 human prostate cancer cells [140] Exhibition of anticancer capability in human lung and leukemia cells [105] Modulated the expression of cyclooxygenase-2 (COX-2) and I B in human colon cancer cells [141] Cytotoxicities Inhibitory effect on activator protein-1, nuclear factor-B, and mitogen-activated protein kinases activation [105,142] Prevented the urinary tract infections [143] Showed potential inhibitory effect against bacteria involved in dental caries and periodontal diseases [147,148] Exhibited potent biological activity by inhibiting adherence of uropathogenic isolates of P-fimbriated Escherichia coli bacteria to cellular surfaces containing -Gal(1 4)--Gal receptor sequences similar to those on epithelial cells in the urinary tract [149,150] Antimicrobial Activities…”
Section: Biosynthesis Pathways Of Anthocyanins and Flavonoids (Fig 3mentioning
confidence: 99%
“…were found to induce apoptosis in cancer cells and to inhibit human leukemia [4][5][6][7] and breast [5,8], colon [4-7, 9, 10], lung [7], and prostate [5,11,12] cancer cells in vitro. Vaccinium has been an important source of food and pharmaceutical ingredients coupled with have high antioxidant potential [10,13,14]. The berries of many Vaccinium species are harvested for household consumption and commercial sale, particularly of bilberry (V. mytillus L.) [6,9], rabbiteye blueberry [10], lowbush blueberry (V. angustifolium Aiton) [11,12], cranberry (V. macrocarpon Aiton) [4,5,7], and highbush cultivated blueberry (V. corymbosum L.) [10,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include such foods as pomegranate, blueberries, green tea, salmon, broccoli, garlic and gugi berries. Though the term "superfood" is considered to be more of a marketing term, professionals admit that these types of foods are nutraceutical-rich and have been shown to be healthy and disease preventing in animal trials [92,93] as well as some human clinical trials [94][95][96]. Many of the nutraceuticals contained in the superfoods are broken down in the human gut by the microbiota and this transformation often turns them into physiologically active materials.…”
Section: Diet-induced Changes In the Microbiome Affect Holobiont Physmentioning
confidence: 99%
“…Alguns estudos relatam que embora as antocianinas estejam presentes em maiores concentrações, esses compostos são menos efetivos do que os elagitaninos (ROSS et al, 2007). No entanto, Yi et al (2005) analisaram frações ricas em antocianinas de mirtilo e esses compostos foram relatados como sendo os responsáveis pelo efeito antiproliferativo em linhagens celulares de câncer de cólon. Malik et al (2005) avaliaram o efeito in vitro e in vivo do suco de romã na inibição do crescimento de células humanas de carcinoma de próstata.…”
Section: Tabela 18 Identificação Dos Derivados De áCido Elágico E Elunclassified